2005
DOI: 10.3168/jds.s0022-0302(05)73003-4
|View full text |Cite
|
Sign up to set email alerts
|

Tie-Stall Design and its Relationship to Lameness, Injury, and Cleanliness on 317 Ontario Dairy Farms

Abstract: The objective of this study was to identify relationships between tie-stall design and selected cow-based injury, lameness, and cleanliness measurements. All lactating dairy cows (n = 17,893) from 317 Ontario tie-stall dairy farms were evaluated once between March and September 2003. Stall dimensions were recorded and cows were scored for neck and hock lesions, broken tails, back arch, hind claw rotation, and udder and hind limb cleanliness. Neck lesions were significantly associated with tie-rail height. Hock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
107
6
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 12 publications
17
107
6
3
Order By: Relevance
“…This suggests that free stalls expose cattle to adverse environmental conditions, which are important to the epidemiology of lameness (Cook and Nordlund, 2009). The prevalence of lameness varies in the studies made in different countries of the world, ranging from 20% (Espejo et al, 2006) to 48% (Dippel et al, 2009) for loose housing systems and from 1% to 21% in tied systems (Cook, 2003;Sogstad et al, 2005, Zurbrigg et al, 2005. In Romania data are available only for the lameness prevalence in tie-stall housing and it is similar with that obtained in this study (Popescu et al, 2010b).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This suggests that free stalls expose cattle to adverse environmental conditions, which are important to the epidemiology of lameness (Cook and Nordlund, 2009). The prevalence of lameness varies in the studies made in different countries of the world, ranging from 20% (Espejo et al, 2006) to 48% (Dippel et al, 2009) for loose housing systems and from 1% to 21% in tied systems (Cook, 2003;Sogstad et al, 2005, Zurbrigg et al, 2005. In Romania data are available only for the lameness prevalence in tie-stall housing and it is similar with that obtained in this study (Popescu et al, 2010b).…”
Section: Resultssupporting
confidence: 85%
“…Body lesions were observed especially at the animals' hock, without significant differences (P>0.05) between the two housing systems. However, in both systems the prevalence of body lesions was lower than it was found in other studies (Weary and Taszkun, 2000;Zurbrigg et al, 2005).…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…The prevalence of lameness had wide range in the assessed farms, but not exceeding 16.2% per farm. Lameness in cattle is highly related to the bed surface, bedding material, cleanliness, hock skin alterations, regular exercise and feeding management (21,23,24,25) -factors observed in poor condition in the assessed farms.The measures of criterion "Absence of disease", ocular discharge, diarrhea, vulvar discharge, dystocia, percentage of downer cows and mortality rate exceeded the warning and alarm threshold set up by the protocol. The study conducted in Serbia revealed similar findings as regards the percentage of animals with ocular discharge, diarrhea, dystocia and mortality rate (11), while the Romania (13,16) were lower for all parameters than ours.…”
mentioning
confidence: 99%